DATABASE FORENSIC ANALYSIS ALGORITHMS (International Journal of Engineering and Computer Science, 2017)
In today’s era database plays an important role in every field like computer science, business, administration, medical, e-education etc. Due to this probability of database tampering is increased.  So it is main responsibility of database developer to think about database security and try to detect tampering in database. In order to do this various database forensic analysis techniques are available. In this paper we are presenting overview of two of them. First is one way hashed key algorithm and second is tiled bitmap algorithm. Tampering of a database can be detected through the use of cryptographically-strong hash functions. Subsequently-applied forensic analysis algorithms can help determine when, what, and perhaps ultimately who and why. This paper presents a novel forensic analysis algorithm, the Tiled Bitmap Algorithm, which is more efficient than prior forensic analysis algorithms. It introduces the notion of a candidate set (all possible locations of detected tampering(s)) and provides a complete characterization of the candidate set and its cardinality.